«Mi sono stancato dell’Italia, ma ne sono irresistibilmente attratto»: Le ultime opere di Cecil Pinsent (1937-1958) - Fecchio, Lorenzo (Studi e ricerche di storia dell’architettura, 2025)
The English architect Cecil Ross Pinsent (1884-1963) is best known as a garden designer. Working for the Anglo-American community that lived on the hills of Florence, Pinsent designed some of the most important formal gardens of the early Twentieth century. Much less explored, however, is Pinsent’s career after 1937, when he decided to leave Italy, the country where he had taken roots and built his professional fortune, and return to England. This essay retraces the years that followed his move from Florence, examining Pinsent’s personal journey, his relationship with Italy, his activity as Monuments Man during WW2, and the last buildings he designed, thanks to the extensive body of unpublished documents collected at the Royal Institute of British Architects (RIBA), Villa I Tatti (Harvard University), and Hull University.